2019
DOI: 10.1101/571455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noroviruses subvert the core stress granule component G3BP1 to promote viral VPg-dependent translation

Abstract: 148) 1Knowledge of the host factors required for norovirus replication has been hindered 2 by the challenges associated with culturing human noroviruses. We have combined 3 proteomic analysis of the viral translation and replication complexes with a CRISPR 4 screen, to identify host factors required for norovirus infection. The core stress 5 granule component G3BP1 was identified as a host factor essential for efficient 6 human and murine norovirus infection, demonstrating a conserved function across 7 the Nor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In the second model, SARS‐CoV‐2 proteins may induce the formation of unique types of granules, either independently of stress granules or via initial recruitment to but subsequent separation from stress granules. Support for this type of model exists for unrelated viruses, whereby viral proteins actually induce stress granules that differ from canonical stress granules in their molecular composition or co‐opt stress granule components for viral replication or viral mRNA translation 13‐16,41,42 . In the third model, N protein may inhibit the formation of stress granules by physical interaction and sequestration of key stress granule components, including G3BP1, G3BP2, and hnRNPA1.…”
Section: Multiple Distinct Lines Of Evidence Connect the N Protein Wimentioning
confidence: 99%
“…In the second model, SARS‐CoV‐2 proteins may induce the formation of unique types of granules, either independently of stress granules or via initial recruitment to but subsequent separation from stress granules. Support for this type of model exists for unrelated viruses, whereby viral proteins actually induce stress granules that differ from canonical stress granules in their molecular composition or co‐opt stress granule components for viral replication or viral mRNA translation 13‐16,41,42 . In the third model, N protein may inhibit the formation of stress granules by physical interaction and sequestration of key stress granule components, including G3BP1, G3BP2, and hnRNPA1.…”
Section: Multiple Distinct Lines Of Evidence Connect the N Protein Wimentioning
confidence: 99%
“…3A, Table S6) were enriched in IFNγ-treated and norovirus infected cells compared to mock conditions. Among the targeted genes were G3bp1, Sptcl1 and Sptcl2 which are required for efficient norovirus replication (21, 4547). Among the genes identified as candidates for enhancing IFNγ-induced inhibition of norovirus replication were Iqgap1 and Ufc1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mock or IFNγ treatment alone revealed genes essential for cell survival, which were not studied further. Analysis of cells treated with IFNγ and infected with norovirus revealed genes essential for efficient norovirus replication (21, 4547) and the genes that regulate responses to IFNγ such as Ufc1 and Uba5 . We further showed that Wipi2 and Atg9a are required for efficient IFNγ-induced inhibition of norovirus replication; we were able to confirm a role for WIPI2B in control of T. gondii in addition to norovirus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation coefficient was calculated on grouped Polysomal and Total data using the Pearson method in GraphPad. Primers are listed in the supplementary data.Biorthogonal labelling for characterisation of de novo proteome Stable isotope labelling of amino acids in RAW264.7 cells culture was performed as described in(82) and carried out in high-glucose DMEM lacking arginine and lysine (Sigma-Aldrich) supplemented with dialysed 10% FBS, 1% L-Glutamine, 1x NEAA, 10mM HEPES and 1x penicillin/streptomycin. RAW264.7 cells were maintained in SILAC media supplemented with Light (R0K0), Medium (R6K4) or Heavy (R10K8) Arginine and Lysine (Cambridge Isotope Laboratories) for 5 passages, ensuring complete incorporation of the different isotopes.…”
mentioning
confidence: 99%
“…Validation IP was performed similarly but the AHA-labelling time was increased to 2 hours to improve labelling and enrichment. Eluted fractions were submitted for mass spectrometry analysis at the University of Bristol Proteomics Facility as described in(82). SILAC pooled samples were run on an SDS-PAGE gel and each gel lane cut into 10 equal slices.…”
mentioning
confidence: 99%